1996
DOI: 10.1021/bi953012j
|View full text |Cite
|
Sign up to set email alerts
|

The Paradoxical Influence of Thymine Analogues on Restriction Endonuclease Cleavage of Oligodeoxynucleotides

Abstract: Thymine residues in the DNA of eucaryotes may be replaced occasionally by uracil (U) or 5-(hydroxymethyl)uracil (H) as consequences of dUMP misincorporation or thymine oxidation, respectively. In this study, we constructed a series of 44-base oligonucleotides containing site-specific U or H residues and 5'-fluorescein labels in order to probe the influence of such modifications on sequence-specific DNA-protein interactions using several type II restriction endonucleases. We find that substitution within the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…In this study, the purchased synthetic phosphorothioate is a mixture of R p -form and S p -form diastereomers, and our results could be the fastest one among the R p -form cleavage and S p -form cleavage. We have observed that some substitutions increased cleavage efficiencies, such as XbaI-S7, SpeI-S2, SpeI-S3, SpeI-S5, SpeI-S6 and SpeI-S7, being consistent with previous reports [4] . The exact mechanism for such enhancement has not been given.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the purchased synthetic phosphorothioate is a mixture of R p -form and S p -form diastereomers, and our results could be the fastest one among the R p -form cleavage and S p -form cleavage. We have observed that some substitutions increased cleavage efficiencies, such as XbaI-S7, SpeI-S2, SpeI-S3, SpeI-S5, SpeI-S6 and SpeI-S7, being consistent with previous reports [4] . The exact mechanism for such enhancement has not been given.…”
Section: Resultssupporting
confidence: 93%
“…The majority of type II REs remains unexplored due primarily to the absence of structural information. To identify particular molecular interactions between REs and their duplex substrates and to obtain an understanding about the nuclease cleavage mechanisms, selective substitutions of nucleotide analogues for particular nucleotides of RE recognition sequences have been utilized extensively [4] , [5] , [6] , [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation of 5 m C to hm C could impact DNA-protein interactions because replacement of the hydrophobic methyl group by the hydrophilic hydroxymethyl group may prevent or alter the binding of proteins having hydrophobic binding clefts for the 5 m C methyl group. Recently, we demonstrated that replacement of T by hm U residues increases the dissociation rate of restriction nucleases from the cleaved substrates (29).…”
Section: Discussionmentioning
confidence: 99%
“…72 Overall, the increase in stability to endonuclease degradation appears to be both larger and more consistent than that observed previously with other 5-position modifications. 86,87,88,89,90 …”
Section: Increased Nuclease Resistancementioning
confidence: 99%